2018
DOI: 10.1016/j.tjog.2018.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Multiple metastatic gestational trophoblastic disease after a twin pregnancy with complete hydatidiform mole and coexisting fetus, following assisted reproductive technology: Case report and literature review

Abstract: Cases of CHMCF following ART may also have higher malignant potential and higher risk of GTD development and become more aggressive biologically. The clinical course of CHMCF after ART seems to be almost the same as that without ART based on the results of literature review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 16 publications
1
7
0
1
Order By: Relevance
“…Sebire et al reported that only four cases of GTN occurring in 77 cases of CHMCF pregnancies (5.2%) required multidrug combination chemotherapy [ 5 ], suggesting CHMCF does not present a high risk for GTN. However, previous case reports describe diagnoses of high-risk GTN after CHMCF or cases requiring multidrug combination chemotherapy for GTN (presumed to be high-risk GTN) [ [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] ]. In six of 12 cases (50%), including the present case, single-agent chemotherapy was given as the initial chemotherapy for PTD.…”
Section: Discussionmentioning
confidence: 99%
“…Sebire et al reported that only four cases of GTN occurring in 77 cases of CHMCF pregnancies (5.2%) required multidrug combination chemotherapy [ 5 ], suggesting CHMCF does not present a high risk for GTN. However, previous case reports describe diagnoses of high-risk GTN after CHMCF or cases requiring multidrug combination chemotherapy for GTN (presumed to be high-risk GTN) [ [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] ]. In six of 12 cases (50%), including the present case, single-agent chemotherapy was given as the initial chemotherapy for PTD.…”
Section: Discussionmentioning
confidence: 99%
“…A rather rare entity is the presence of a twin pregnancy with a molar pregnancy (either CHM or PHM) and coexisting fetus. Several case reports and series have been published in this subject matter [6], [7], [8], including metastasis during pregnancy [9,2] or after pregnancy [10], [11], [12], [13], [14], [15]. A twin pregnancy with CHM can be differentiated from a twin pregnancy with PHM by the presence of viable fetus as in the latter case the fetus is usually anomalous or dead.…”
Section: Discussionmentioning
confidence: 99%
“…Anteriormente, el manejo de la gestación gemelar compuesto por mola hidatiforme completa y feto vivo consistía en la terminación temprana del embarazo (5,6). Sin embargo, la continuidad de la gestación se ha convertido en una opción viable en el siglo XXI, apoyada por una serie de casos japoneses en la que los investigadores notaron que el riesgo de malignidad no cambia con la edad gestacional avanzada, pero es importante la adecuada monitorización de complicaciones (7).…”
Section: Discussionunclassified